Global food policy report 2023: Rethinking food crisis responses - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
This decade has been marked by multiple, often overlapping, crises. The COVID-19 pandemic, natural disasters, and the ongoing war in Ukraine have all threatened the fabric of our global food systems. But opportunities can be found amid crises, and the world’s food systems have demonstrated surprising resilience. With new evidence on what works, now is the time to rethink how we address food crises. Better prediction, preparation, and resilience building can make future crises less common and less devastating, and improved responses can contribute to greater food security, better nutrition, and sustainable livelihoods.